A fiscal job? An analysis of fiscal policy and the labor market - Elva Bova; Christina Kolerus; Sampawende Tapsoba (IZA Journal of Labor Policy, 2015)
This paper examines the role of fiscal policies in the dynamics of the labor market. Through the lenses of Okun's Law, we assess how fiscal policy instruments as well as fiscal consolidation and expansion episodes affect labor market outcomes. Using a panel of 34 OECD countries over the period 1985 - 2013, we find that fiscal consolidation has a sizeable, positive and robust impact on the Okun's coefficient. This effect is particularly strong for expenditure based consolidations, suggesting that a reduction in the size of the government increases the responsiveness of employment to output and is not altered by an expansionary or recessionary position in the business cycle. Interestingly, we find no impact of fiscal expansion on the Okun's coefficient nor for specific fiscal instruments.
Keywords: E24; E32; E62; 330; Okun's Law; Fiscal policy